Pandemi Covid 19 dan Perubahan Pola Pembayaran dalam Industri Pariwisata di Kabupaten Banyumas Berbasis Cashless Management System - Muhammad Yamin; Ratna Ningtyas; I Putu Arya Aditia Utama (Review of International Relations, 2023)
This study aims to determine changes in payment patterns in the tourism industry in the Banyumas district based on a cashless management system during the Covid-19 pandemic. Tourism is one of the sectors affected by the Covid-19 pandemic. In response to the Covid-19 pandemic, Indonesian tourism has quickly adapted to the various changes that have occurred, including in transaction patterns. Banyumas Regency is one of the areas that is well-known for its tourism industry potential, so the author will further analyze the efforts of the Banyumas tourism industry in dealing with changes in transaction patterns that occurred during the Covid-19 pandemic. This study uses the concept of a cashless management system in analyzing the efforts of the Banyumas tourism industry in responding to changes in transaction patterns that occur. The method used in this paper is qualitative with a case study approach. The data collection technique used the library study method. Research shows that the Banyumas tourism industry responds to changes in transaction patterns by implementing a cashless management system to create a sense of security and comfort for tourists who want to travel in the Banyumas area. In addition, implementing a cashless management system is also carried out to accommodate people who wish to make non-cash transactions, and indirectly, applying a cashless management system will form a transparent and accountable financial climate.